Tribologia de cerâmicos dissimilares no deslizamento em água. Estudos de caso : Si3N4-SiC, Si3N4-Al2O3, Si3N4-ZTA, Al2O3-SiC, ZrO2-SiC, ZrO2-Al2O3 e ZrO2-ZTA - Strey, Nathan Fantecelle (2015)
Under certain conditions, the sliding of ceramic materials under water lubrication shows ultra-low friction coefficient (μ<0,01), which characterizes a state of superlubricity. The high load capacity and energetic efficiency of these tribosystems, together with its reduced ambiental impact, are superior characteristics if compared to the traditional oil-lubricated metallic tribological pairs. Similar pairs of silicon nitride (Si3N4) or silicon carbide (SiC) were widely studied and are pointed as having the greatest tribological performance, while similar pairs of oxide ceramics, such as alumina (Al2O3) and zirconia (ZrO2), usually show poor performance (low load capacity and high friction coefficient) in water-lubricated conditions. Literature is scarce concerning to dissimilar ceramic pairs sliding in water and in explanations about the nature of the superlubricity phenomenon. In that context, an investigation of the tribological behavior of seven different combinations of dissimilar ceramic materials, oxide (Al2O3, ZrO2 and zirconia-toughened alumina – ZTA) and non-oxide (Si3N4 and SiC), using ballon- disc test configuration was performed with the objective of identifying pair of materials and operational conditions where superlubricity occurs as well as to determine present wear mechanisms and lubrication regimes. In the study of lubrication, an experimental verification of a model that incorporates effects from surface topography and electrical double layer forces was done. Of the seven studied pairs, five showed superlubricity (Si3N4-SiC, Si3N4- Al2O3, Si3N4-ZTA, Al2O3-SiC and ZrO2-SiC), noting that for the last three listed there were no previous reports in the literature. For a wide range of normal loads and sliding speeds, the other two pairs (ZrO2-Al2O3 and ZrO2-ZTA) showed transitions between mild and severe wear regimes, with respective transitions on frictional behavior. Regarding to mean contact pressure, a parameter that can be interpreted as the load capacity of a bearing, the pair ZrO2-SiC was superior, with the magnitude at least two times greater than the others. From the verification of the lubrication model, the conclusion was that every pair that showed superlubricity operated at a regime of mixed lubrication. In a general way, hydrodynamic pressure, assisted by effects of the surface topography, was important in determining the load capacity of the lubricating fluid film, while electrokinetic forces were negligible. For these pairs, tribochemical wear mechanisms led to the formation of tribofilms on the sliding surfaces. Maintaining ultra-low friction coefficients, even in mixed lubrication regime, support the idea that the tribofilms are vital for the occurrence of the phenomenon.